Semi-processed fruit and berries : as raw materials in the food-processing and catering industries - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre, 1978)
This book explains a market study on frozen, canned and temporarily preserved fruit and berries for industrial catering use in France, Germany FR, Netherlands, UK, Canada, and Japan. Gives data and comments on supply and demand patterns and trends, market characteristics and marketing recommendations; for each country surveyed covers production, foreign trade end-user sectors, market requirements, competition, distribution, market access, market prospects; also gives useful addresses.
Includes bibliographical references: p. 143-144.
asm 22/01/2019
Loans
Keywords: Fruit--Processing; Berries